Youth and Adult Education - brief analysis of the Brazilian panorama (Research, Society and Development, 2022)
Youth and Adult Education is a specific modality of Brazilian Education that comprises people over fifteen years old who have not completed Basic Education in a normal time or who have never attended school. The Federal Constitution of 1988 recognizes education as a right for everyone, regardless of age, which unfolds into public policies that aim to guarantee this right with equal opportunities and equity in education. Given the heterogeneity that EJA presents and the quantity of demand, it is necessary to highlight this teaching modality for reflection and discussions. In this context, the study justifies this need and aims to analyze the Brazilian EJA, highlighting its historical context; punctuating past and current public policies; and drawing a current overview of the issue. For this, a qualitative research was used. Regarding the objectives, it is an exploratory and descriptive research and regarding the research procedures, the study was characterized as bibliographical. The research was carried out in a virtual environment, in reliable databases, with published scientific articles and also includes virtual environments for studies and research in Law for theoretical basis, as well as in Laws and the Federal Constitution of the Republic and Pedagogy books. After the analytical reading and highlighting of the main aspects, the textual production was elaborated in three titles that are related and complement: Youth and Adult Education, EJA; Historical-legal context of EJA in Brazil and Panorama of EJA in Brazil. The author sought to maintain impersonality, but his impressions permeate the conclusions set out in the Final Considerations.